The Reality of Distance Education for Science and English language courses in light of the Corona pandemic from the point of view of primary school teachers in Jordan - Alsubue, Magda Khalf; Dalabih, Abdul-Razzaq Abdul-Hafiz; Odibat, Anas Adnan Mohamad; Alsarayreh, Eyad Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of distance learning in teaching science and the English language in light of the Corona pandemic from the point of view of primary school teachers in Jordan in Karak Governorate, and the study was based on the descriptive and analytical approach, and the study population consisted of 280 teachers working in basic government schools in the governorate of Karak, the study sample reached (74) male and female teachers, who were randomly selected. The results of the study showed that the degree of employing distance learning for elementary school teachers in Jordan (Karak Governorate) was high, with a mean (3.89). The results also showed that there are no statistically significant differences in the reality of distance learning according to the variables (gender, academic qualification, and job experience), and the study recommended the necessity of providing devices for distance learning, providing the Internet for all students and teachers, and holding courses and workshops for teachers and students to enlighten them of the importance of this system.